Citizen participation in times of crisis: Understanding participatory budget during the COVID-19 pandemic in Nepal - Bhusal, Thaneshwar (UI Scholars Hub, 2020)
This research assumes that various forms and scales of lockdowns and social distancing measures have limited local decision-makers’ ability to reach out to communities as part of their mandatory annual participatory budgeting processes. Building upon this proposition, this article assesses Nepal’s local budgeting process of 2020 to understand the degree to which it succeeded (or failed) in incorporating citizen’s voices in the annual handbook of local public policies and budgets. The research followed a qualitative case study research methodology. It generated interviews with participants including ordinary people, local politicians, and bureaucrats from 20 different municipalities and a federal ministry in Nepal. Other textual data (official publications, field notes and observational scripts) provided complementary evidence to answer the research questions. Findings suggest that the coronavirus pandemic has played significant roles in limiting ordinary people’s democratic right to participate in local decision-making yet flaws in institutional design and unpredictable mayoral power contributed to delaying the annual budget approval process. The research contributes to the literature on participatory governance in developing countries, with some practical suggestions to increase citizen engagement chances in times of crisis.